The University in Dissent : Scholarship in the corporate university. - Rolfe, Gary (Research into Higher Education., 2012)
The rise of corporatism in the North American University was charted by Bill Readings in the mid nineteen-nineties in his book The University in Ruins. The intervening years have seen the corporate university grow and extend to the point where its evolution into a large business corporation is seemingly complete. Rolfe's book examines the factors contributing to the transformation of the university from a site of culture and knowledge to what might be termed an 'information factory', and explores strategies for how, in Readings' words, members of the academic community might continue.